2017
DOI: 10.1074/jbc.m117.805283
|View full text |Cite
|
Sign up to set email alerts
|

Lysine acylation in superoxide dismutase-1 electrostatically inhibits formation of fibrils with prion-like seeding

Abstract: The acylation of lysine residues in superoxide dismutase-1 (SOD1) has been previously shown to decrease its rate of nucleation and elongation into amyloid-like fibrils linked to amyotrophic lateral sclerosis. The chemical mechanism underlying this effect is unclear, hydrophobic/steric effects electrostatic effects. Moreover, the degree to which the acylation might alter the prion-like seeding of SOD1 has not been addressed. Here, we acylated a fraction of lysine residues in SOD1 with groups of variable hydroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 57 publications
3
42
0
Order By: Relevance
“…Transmission electron microscopy (TEM) revealed that G93A ThT binding was associated with fibril formation, whereas G93A-S32 TEM structures were sparsely distributed amorphous aggregates (Fig. 1C ), ruling out the generation of ThT negative SOD1 fibrils as has been reported 24 .
Figure 1 S32 substitution mitigates aggregate formation of purified SOD1 mutants and lowers their stability.
…”
Section: Resultssupporting
confidence: 61%
“…Transmission electron microscopy (TEM) revealed that G93A ThT binding was associated with fibril formation, whereas G93A-S32 TEM structures were sparsely distributed amorphous aggregates (Fig. 1C ), ruling out the generation of ThT negative SOD1 fibrils as has been reported 24 .
Figure 1 S32 substitution mitigates aggregate formation of purified SOD1 mutants and lowers their stability.
…”
Section: Resultssupporting
confidence: 61%
“…The agent employed for acetylation of SOD1 in vitro as well as the site(s) of acetylation influenced the type of aggregates formed [152]. SUMOylation at K75 increased aggregation of mutant (and wild-type) SOD1 [153,154] (Table 6 and Figure 6).…”
Section: Sod1 Ptms and Propensity For Aggregationmentioning
confidence: 99%
“…Recently, we have also con rmed the declined levels of Sirt3 in the brain tissues of several scrapie infected mice and in SMB-S15 cells, leading to increases of acetylating forms of SOD2 and ATP5β that subsequently induce increase of intracellular ROS and reduction of ATP [20]. Aberrant alterations of acetylation modi cations for other proteins have been also found in the brain tissues or the models in vitro of several neurodegenerative diseases, e.g., tau, microtubules, SOD1 [21][22][23]. However, the global change of protein acetylation in the brain tissues of prion diseases remains unsettled.…”
Section: Introductionmentioning
confidence: 60%